Is wetter better? Exploring agriculturally-relevant rainfall characteristics over four decades in the Sahel. (11th February 2021) - Porkka, Miina; Wang-Erlandsson, Lan; Destouni, Georgia; Ekman, Annica M L; Rockström, Johan; Gordon, Line J
Abstract: The semi-arid Sahel is a global hotspot for poverty and malnutrition. Rainfed agriculture is the main source of food and income, making the well-being of rural population highly sensitive to rainfall variability. Studies have reported an upward trend in annual precipitation in the Sahel since the drought of the 1970s and early '80s, yet farmers have questioned improvements in conditions for agriculture, suggesting that intraseasonal dynamics play a crucial role. Using high-resolution daily precipitation data spanning 1981–2017 and focusing on agriculturally-relevant areas of the Sahel, we re-examined the extent of rainfall increase and investigated whether the increases have been accompanied by changes in two aspects of intraseasonal variability that have relevance for agriculture: rainy season duration and occurrence of prolonged dry spells during vulnerable crop growth stages. We found that annual rainfall increased across 56% of the region, but remained largely the same elsewhere. Rainy season duration increased almost exclusively in areas with upward trends in annual precipitation (23% of them). Association between annual rain and dry spell occurrence was less clear: increasing and decreasing frequencies of false starts (dry spells after first rains) and post-floral dry spells (towards the end of the season) were found to almost equal extent both in areas with positive and those with no significant trend in annual precipitation. Overall, improvements in at least two of the three intraseasonal variables (and no declines in any) were found in 10% of the region, while over a half of the area experienced declines in at least one intraseasonal variable, or no improvement in any. We conclude that rainfall conditions for agriculture have improved overall only in scattered areas across the Sahel since the 1980s, and increased annual rainfall is only weakly, if at all, associated with changes in the agriculturally-relevant intraseasonal rainfall characteristics.